PERAN MAHKAMAH INTERNASIONAL DALAM INTERORETASI DAN PENYELESAIAN PERJANJIAN INTERNASIONAL - Kinayah Ashifa; Yosaphat Diaz; Reza Ramdan Gumilar; Febby Annisa Qutrunnada; Mayzara Sari Fitria (JOURNAL SAINS STUDENT RESEARCH, 2026)
The International Court of Justice (ICJ) holds a strategic position in upholding and maintaining the international legal order, particularly in the context of interpreting and resolving disputes arising from international treaties between states. As the highest judicial institution under the auspices of the United Nations (UN), the ICJ plays a crucial role in ensuring the implementation of the principle of pacta sunt servanda and upholding the principle of peaceful dispute resolution as the foundation of civilized relations between states. This article aims to conduct a normative juridical study of the ICJ's role in interpreting the provisions of international treaties and to assess the extent to which its decisions are able to achieve legal certainty and justice in the international legal system.